2015
DOI: 10.1007/s10142-015-0457-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-based discovery of AP2/ERF transcription factors related to temperature stress in tea plant (Camellia sinensis)

Abstract: Tea plant (Camellia sinensis) is an important natural resource for the global supply of non-alcoholic beverage production. The extension of tea plant cultivation is challenged by biotic and abiotic stresses. Transcription factors (TFs) of the APETALA 2 (AP2)/ethylene-responsive factor (ERF) family are involved in growth and anti-stresses through multifaceted transcriptional regulation in plants. This study comprehensively analyzed AP2/ERF family TFs from C. sinensis on the basis of the transcriptome sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 63 publications
6
42
0
Order By: Relevance
“…In summary, the RPKM values revealed that the four tea plant cultivars differed in the expression of CsNAC genes. These tea plant cultivars are grown in different regions of China [39, 40], and the differences may occur on the individual evolution of different cultivars.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, the RPKM values revealed that the four tea plant cultivars differed in the expression of CsNAC genes. These tea plant cultivars are grown in different regions of China [39, 40], and the differences may occur on the individual evolution of different cultivars.…”
Section: Resultsmentioning
confidence: 99%
“…The completed transcriptome sequencing of tea plant provides an opportunity to identify gene families at the transcriptome level [39]. Recent studies have identified and analyzed 89 AP2/ERF, 50 WRKY, 16 HSF, and 18 bZIP genes in tea plant; the roles of these genes in response to adversity stresses were also elucidated [4043]. To date, detailed analysis of NAC family genes in tea plant remains to be conducted.…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of Dof TFs in response to abiotic stress has been investigated in other plants. Some researchers have also analyzed other TFs families in tea plant [34, 35]. There is, however, the regulatory mechanism of Dof TFs in tea plant which is not completely understood till now.…”
Section: Introductionmentioning
confidence: 99%
“…ERFs are members of one of the largest transcription factor families, which is considered a superfamily, and is involved in plant biological and abiotic stress responses (Licausi et al, 2013;Min et al, 2012;M€ uller and Munn e-Bosch, 2015;Phukan et al, 2017). It has been reported that CsAP2/ERF(APETALA2/ERF) may play important roles in the abnormal temperature stress response in Camellia sinensis (Wu et al, 2015). TERF2/LeERF2 enhance the freezing tolerance of Nicotiana tabacum and Solanum lycopersicum through ethylene biosynthesis and the ethylene signaling pathway (Zhang and Huang, 2010).…”
mentioning
confidence: 99%